Pengaruh Dewan Komisaris Independen, Komite Audit, Kepemilikan Keluarga dan Pengungkapan Sukarela Terhadap Biaya Utang - Rizki Aditiya; Agus Sihono (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the effect of Independent Board of Commissioners, Audit Committee, Family Ownership, and Voluntary Disclosure on Debt Costs in Basic Materials manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. Using purposive sampling and multiple linear regression analysis, the results show that the Independent Board of Commissioners and Family Ownership have a negative and significant effect on debt costs, while the Audit Committee, measured by meeting frequency, has a significant positive effect, and Voluntary Disclosure has no significant effect. These findings indicate that increased independent supervision and family control can reduce debt costs, but a high frequency of audit committee meetings can create a greater perception of risk in the eyes of creditors. This study has important implications for management and regulators in improving the quality of corporate governance and supervision to reduce debt costs.